Hypertensive Disorders of Pregnancy Across the Range of Gravidity. - Parveen Naveed; Tabassum Ikram; Perveen, Saima; Saima Ali; Fehmida; Uzma Ahmad (Journal of Postgraduate Medical Institute, 2025)
Objective: To compare the pre-eclampsia and eclampsia frequency in Primigravida and multigravida women who presented to the labor room of Saidu Teaching Hospitals, Swat. Methodology: The study was a retrospective cross-sectional case study between 1st January 2024 to 31st December 2024 involving 12498 admissions to the labor room by pursuing the convenience sampling method. Pregnant women who had either eclampsia and/or pre-eclampsia and were aged at ³18 years during the time of study in the labor room were the study subjects. The study excluded patients having protein losing enteropathy, conditions of uric acid or disorders of the kidneys such as nephrotic syndrome, diabetes Mellites and liver diseases. Statistical analysis included descriptive statistics, chi square test, and odds ratio calculations to compare the prevalence of hypertensive disorders between Primigravida and multigravida women. Results: The frequency of preeclampsia and eclampsia was 3.3% among Primigravida women and 12.8% among multigravida women (p<0.05). Women who had more than one pregnancy were much more likely to get these conditions, especially those over 35 years old. Limited access to antenatal care and increasing maternal age were recognized as significant factors contributing to the elevated prevalence among multigravida women. Conclusion: In this study, multigravida women are substantially more likely to experience hypertensive disorders during pregnancy. The results show that improved prenatal care is necessary to effectively address the increasing burden of these conditions.